ALTRUISM IN JODI PICOULT'S MY SISTER'S KEEPER - Ganap, Brenda Amelia; Oroh, Elizabeth; Mogea, Tini (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The main goal of this research is to uncover examples of altruism in the novel “My Sister’s Keeper” by Jodi Picoult. This research uses qualitative methods, focusing on data in the form of words or images rather than numerical data. Data collection involves drawing information from the novel itself as a primary source, supplemented by secondary sources such as books and online materials to support the analysis. The analysis uses the objective approach, given that the required data is found in literary works, especially the novel “My Sister’s Keeper.” The results reveal that Anna Fitzgerald embodies altruistic qualities. Anna constantly directs her focus to the well-being of her older sister, Kate Fitzgerald, rather than prioritizing herself. She actively helped Kate recover from her illness, donating her blood, bone marrow and other bodily elements to keep her older sister alive